2010
DOI: 10.4103/0378-6323.66576
|View full text |Cite
|
Sign up to set email alerts
|

Erythroderma in children

Abstract: Although erythroderma is a well-recognized entity in the adult age groups and has been studied by various authors, there is a paucity of studies on erythroderma in the pediatric age group. It poses a greater challenge to the dermatologist and pediatrician because of its potential life threatening nature. In a study conducted by us in a large Indian hospital to delineate the causes of neonatal and infantile erythroderma, the causes identified were infections (40%), ichthyosiform erythroderma (25%), atopic derma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0
9

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(50 citation statements)
references
References 19 publications
2
33
0
9
Order By: Relevance
“…However, the dominance components were higher than the additive component for most of the traits. These results are in conformity with [7,8,9]. In the present investigation, the predominance of non-additive gene action and low narrow sense heritability for most of the yield attributing characters suggesting the importance of heterosis breeding in cucumber.…”
Section: Total Yield Per Plant (G)supporting
confidence: 91%
“…However, the dominance components were higher than the additive component for most of the traits. These results are in conformity with [7,8,9]. In the present investigation, the predominance of non-additive gene action and low narrow sense heritability for most of the yield attributing characters suggesting the importance of heterosis breeding in cucumber.…”
Section: Total Yield Per Plant (G)supporting
confidence: 91%
“…For Soeprono et al, 85% of individuals with AIDS have SD, whereas Berger reported this figure as 36%, Goodman as 32% and Blanes et al as 31% of patients. [92][93][94][95][96][97][98][99][100][101][102] Malassezia spp. is also involved in the development of the disease.…”
Section: Seborrheic Dermatitis and Hivmentioning
confidence: 99%
“…They may be limited to small areas of the body; however, there have been reports of generalized forms and even of erythroderma. [93][94][95][96] The presence of pruritus is variable. The principal complicating factor in the lesions is secondary bacterial infection, which increases the erythema and exudate, local discomfort and lymphadenomegaly close to affected areas.…”
Section: Clinical Diagnosismentioning
confidence: 99%
“…A diagnózis felállí-tása, így az oki terápia alkalmazása sok esetben jelentős kihívást jelent a klinikusok számára (1,2,(4)(5)(6)(7)(8).…”
Section: Diagnózisunclassified